Structure and magnetic properties of nanocompsite Fe–Pt–B ternary alloys - Dianguo Ma; Liantao Cheng; Yanli Zhu; Yanhui Li; Yingmin Wang; Kunio Yubuta; Wei Zhang; Lincai Zhang (Journal of Materials Research and Technology)
Structures and magnetic properties of nanocompsite Fe–Pt–B ternary alloys were investigated in a widely compositional range. A single amorphous phase was formed in a composition range of 0–15 at. % Pt and 20–30 at. % B, while the ranges of fcc-FePt + amorphous, fcc-FePt + Fe2B and L10-FePt + Fe2B/FeB phases were formed out the range of single amorphous. With more than 5 at. % of Pt, the crystallized structure was obtained consisting of nanoscale L10-FePt and Fe2B/FeB phases after annealing except for alloys with 0–10 at. % Pt and 15–25 at. % B. The annealed alloys with ≥10 at. % of Pt exhibit good hard magnetic properties. Increasing the contents of Pt and B were propitious to increase the coercivity (iHc) of the alloys owing to the enlargement of volume fraction for L10-FePt phase. The maximum value of iHc can reach 806 kA/m for the Fe50Pt25B25 alloy after annealing at 843 K for 900 s. Higher Pt content (>20 at. %) led to a decrease of the iHc for alloys with more than 30 at. % B, which is due to the weakened exchange coupling between soft and hard magnetic phases in nanocomposite magnets as the precipitation of FeB phase.